The Effect of Storage Duration on Fruit Juices Made With or Without the Addition of Yeast Towards Its Alcohol Content - Roswiem, Anna Priangani; Septiani, Triayu; Yuliwulandari, Rika (UIN Sunan Gunung Djati Bandung, 2019)
Fruit juice is a healthy beverage. However, we must be careful in handling or consuming such juice, especially in relation to its storage time. The Prophet of Muhammed PBUH in his hadith prohibits to drink fruit juices that have been stored for more than 3 days, as its legal status changes from Halal into Haram.In accordance with the development of science and technology, many methods could be used to measure alcohol content in a sample; such as Gas Chromatography-Mass Spectroscopy method (GC-MS). Therefore the objective of this research was to analyze the alcohol content of various fruit juices made with or without the addition of yeast and being stored within 1, 2, and 3 days using GC-MS, as well as its relation to the hadith Matn of the Prophet Muhammad PBUH regarding its law. Results showed that alcohol (ethanol) content of various fruit juices : red grapes, green grapes, dates, pomegranate and durian, made without the addition of yeast which stored for 3 days, in consecutive order were 0.524; 0.144; 0.214; 0.143 and 0.314% v/v. While alcohol (ethanol) content of various fruit juices : red grapes, green grapes, dates, pomegranate and durian, made with the addition of 10 g/L yeast were and stored for 3 days were 0.618; 0.921; 0.901; 0.575 and 1.202% v/v constitutively. Alcohol content of red grapes fruit juices of 0.524% v/v was the highest alcohol content (in juices) which is still Halal to be consumed.